Morbimortalidad en prematuros en el servicio de Neonatología del Hospital Isidro Ayora en el año 2014 - Flores Bermeo, Mario Alexander (2015)
The maturity to the fetus is the optimal state to trigger labor, tolerate successfully contingencies and adapt quickly and effectively to their new living conditions. Preterm birth is the birth of a new being before 37 weeks of gestation and is one of the biggest problems of neonatal morbidity and mortality. In order to know the causes of morbidity and mortality in preterm infants admitted to the Neonatal Service, a retrospective study based on analysis of 355 live births entered in the register of statistical data in the Hospital General Isidro Ayora of Loja was made during the year 2014; and, from this share the results, and thus help to improve the care and management of preterm infants. Neonatal expenditure was revised finding that in this health house the main causes of morbidity in preterm infants were: respiratory distress syndrome type 2 with 70%, respiratory distress syndrome type 1 with 36% and the neonatal jaundice 30% of cases. While the main cause of death was respiratory distress syndrome type 1 in 69% cases. Also it was known that primarily affected the male gender is 64%; the percentage of premature mortality is 19.7 per 100 admissions and the most affected group was the moderately preterm, according to the classification of prematurity of the World Health Organization. KEYWORDS: morbidity; mortality; preterm infants.